Usability and information architecture in the light of the Top-down approach on the Federal Police Intranet - Belo , Caio de Alcântara Moura; Daher, Daniel; Matias, Márcio (Advanced Notes in Information Science, 2023)
Man's relationship with information and its impact on society has become more complex and intense. Today's society is driven by information; consequently, information systems, computers, and webpages have gained relevance for social, economic, cultural, and political relations. It is in this context, and based on the broad attributions of the Brazilian Polícia Federal, that it developed and made available an intranet homepage for its varied internal public so that, through this homepage, they could produce, access, retrieve and disseminate information in the performance of their professional activities. Based on standardized conditions, usability is an attribute that assesses the effectiveness and efficiency of products, including applications and webpages, concerning user needs. This article aims to analyze the usability of the intranet homepage of the Polícia Federal based on the Top-down information architecture model developed by Rosenfeld and Morville. For this purpose, the theoretical basis that supports such an endeavor was reviewed through bibliographic research. The application of the model for the objective measurement of usability criteria resulted in the observation of full compliance of the structural items of the Polícia Federal intranet's homepage with the minimum usability requirements of the selected archetype.